PENGARUH MODIFIKASI PERMAINAN TRADISIONAL UNTUK KEMAMPUAN MOTORIK KASAR ANAK USIA 5-6 TAHUN DI TAMAN KANAK-KANAK KECAMATAN BUAY MADANG TIMUR KABUPATEN OGAN KOMERING ULU TIMUR - wiwitsalindri wiwit; ulwansyafrudin ulwansyafrudin; Rentioktaria renti (Program Studi Pendidikan Islam Anak Usia Dini (PIAUD), 2023)
Early childhood is also called the Golden Age. At this time the process of developing brain nerve cells is still developing rapidly. The aim of the research is to determine the influence of modified traditional games to improve the gross motor development of children aged 5-6 years in East Buay Madang District. The research method uses a quantitative approach. Based on the table of calculation results using the Wilcoxon ladder test formula, it is known that the calculated t value obtained is 0. The sample at Budi Utomo Kindergarten was 16 children and the significance level was 5% so the t table was 30. The sample at Kartini Kindergarten was 23 children and the significance level was 5 % so that the t table obtained is 73%. The conclusion of research in kindergartens in East Buay Madang District with material on developing modifications to the traditional game Gobak Sodor, it can be concluded that the development of the learning process regarding the traditional game Gobak Sodor is said to be feasible. Research suggestions to introduce more traditional Indonesian games to children to make them more interesting and fun in playing techniques to train self-strategy.